n-1.4n-1=6(n-2.3)

Simple and best practice solution for n-1.4n-1=6(n-2.3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-1.4n-1=6(n-2.3) equation:


Simplifying
n + -1.4n + -1 = 6(n + -2.3)

Reorder the terms:
-1 + n + -1.4n = 6(n + -2.3)

Combine like terms: n + -1.4n = -0.4n
-1 + -0.4n = 6(n + -2.3)

Reorder the terms:
-1 + -0.4n = 6(-2.3 + n)
-1 + -0.4n = (-2.3 * 6 + n * 6)
-1 + -0.4n = (-13.8 + 6n)

Solving
-1 + -0.4n = -13.8 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-1 + -0.4n + -6n = -13.8 + 6n + -6n

Combine like terms: -0.4n + -6n = -6.4n
-1 + -6.4n = -13.8 + 6n + -6n

Combine like terms: 6n + -6n = 0
-1 + -6.4n = -13.8 + 0
-1 + -6.4n = -13.8

Add '1' to each side of the equation.
-1 + 1 + -6.4n = -13.8 + 1

Combine like terms: -1 + 1 = 0
0 + -6.4n = -13.8 + 1
-6.4n = -13.8 + 1

Combine like terms: -13.8 + 1 = -12.8
-6.4n = -12.8

Divide each side by '-6.4'.
n = 2

Simplifying
n = 2

See similar equations:

| C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 | | R+4=12 | | 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) |

Equations solver categories